Supervisi Desain Kemasan Dan E-Marketing Berbasis WEB Teknologi SMS Getaway Produksi Kripik Pisang Bekasi - Novi Fitria Hermiati; Retno Purwani Setyaningrum; Wiji Safitri; Fiqih Maria Rabiatul Hariroh; Dian Rachmawati Afandi (Pandawa : Pusat Publikasi Hasil Pengabdian Masyarakat, 2023)
The rapid development of the internet greatly affects business changes. Many business activities have changed with the availability of the internet today. One of the significant changes in business activity is marketing or marketing. Marketing is a social and managerial process by which individuals and groups obtain what they want and need through creating and exchanging products and value with others. Marketing is also the process of designing and executing the conception, pricing, promotion and distribution of ideas, goods and services to create exchanges that satisfy individual and organizational goals. E-marketing describes company efforts to inform, communicate, promote and market products and services via the internet. Electronic marketing utilizes network technology to coordinate market share research, assist product development, develop strategies and tactics to attract customers, provide online distribution. This web-based marketing system with SMS Gateway facilities can assist companies in capturing new customers and providing optimal service to existing customers. This web-based marketing system with SMS Gateway facilities will later be integrated with a database that will store the required data. Packaging is an important marketing tool, not only as a wrapper but also as a differentiator between the company's products and similar products from competitors. Packaging (packaging) is a process related to the design and manufacture of a container (container) or wrapper (wrapper) for a product. Each product should have an attractive packaging design, containing information on the product name, company name, net weight, expiration date, composition, nutritional content, Indonesian National Standard or SNI, Hazard Analytical Critical Control Point (HACCP) and halal marking. 2. In making the packaging design there are aesthetic and identity factors, there should be the words and the Bananation logo, and use a combination of several colors, and add various images to make the packaging more colorful and catchy so that it is easier for everyone to remember. Security and distribution factors must also be a concern of the company without compromising aesthetic value by using corrugated paper type cardboard on the outside and food grade plastic material on the inside so that it is guaranteed durability in shipping and is also environmentally friendly